Tahapan Perancangan Photobooth AI pada Event Bintang Toedjoe oleh Groovy Event Organizer Jakarta - Dewa Samudra Mahabakti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember, 2025)
Event Organizers continue to innovate by utilizing Artificial Intelligence (AI) to create more interactive experiences. Groovy Event Organizer, through its Event Organizer (R&D) division, has developed various technologies, one of which is Photobooth AI. The main issue in this report is how the R&D division at Groovy Event Organizer designed the AI-based Photobooth. The purpose of this final project is to explain the process of implementing Photobooth AI technology, specifically in Event s organized by Groovy Event Organizer. The research method used is qualitative, with data collection through observation, interviews, documentation, and literature study during a six-month period of practical work experience. The results of the work practice show that the AI Photobooth design process for the Bintang Toedjoe Event includes several systematic stages: the submission of requirements by the client, research and creation ofvisual templates using the OpenArt website, system testing with Qbooth software to ensure the functionality of the Face swap feature, and product implementation during the Event. Although the implementation was running, technical obstacles were found in the form of interference in the system integration with Google Drive, which hampered the distribution of photos via QR Code in real time. In conclusion, the design process has been running in a structured manner, but the technical obstacles that occurred are an important evaluation point.
Reuploud file repositori 13 Apr 2026_Firli_Tata
Keywords: Photobooth AI; Event Organizer; Research and Development